Review of Swarasa Kalpana of Single Drug by Sharangadhara Samhita wsr to Phytochemical Analysis (International Journal of Ayurveda and Pharma Research, 2023)
Sharangadhara Samhita is most important Samhita on Bhaishajya Kalpana (Ayurvedic pharmacy) and considered in Laghutrayee. It consists of three Khand (Division)- Poorva Khand, Madhyam Khand, Uttar Khand. Ayurveda offers personalised treatment according to each patient’s unique Doshavastha. Acharya Charaka has described Chikitsa Chatushpada which includes Bhishak (Physician), Upasthata (Medical Attendant), Rogi (Patient) and Dravya (medicine). The selection of Dravya (medicine) is important step in management of disease. Acharya Charaka has mentioned qualities of Dravya like 1) Bahuta 2) Yogyatam 3) Aanekvidha kalpana 4) Sampat. We use whole drug which contain many chemicals which are separated by Agni (Digestive system). These chemicals are absorbed and move in the body through Rasavaha Strotasa.  They interact with each other and modify gene expression at cellular level. Proper Kalpana (formulations) facilitates better chemical separation, absorption and interaction. Thus, overall efficacy of the drug.Phytochemical analysis includes alkaloids, flavonoids, glycosides, phenols, saponins, sterols, tannins, anthraquinone etc. These are important phytochemicals and termed as active principles responsible for action of drug. Different Bhaishajya Kalpana are used to extract active principles of Dravya with the help of medium like water, oil, alcohol, Ghrita. Panchavidha kashaya Kalpana includes Swarasa (liquid), Kalka (paste), Kwatha (decoction), Hima (cold infusion) and Phanta (hot infusion) and are fundamental Ayurvedic Bhaishajya Kalpana. Churna, Vati, Avaleha, Sneha & Sandhan Kalpana are modified forms of Panchavidha Kashaya Kalpana. Hence review of Swarasa Kalpana of single drug by Sharangadhara Samhita wsr to phytochemical analysis is taken.